2023
DOI: 10.1051/0004-6361/202245153
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS-MUSE: Detection and Bayesian classification of ~40 000 ionised nebulae in nearby spiral galaxies

Abstract: In this work, we present a new catalogue of > 40000 ionised nebulae distributed across the 19 galaxies observed by the PHANGS-MUSE survey. The nebulae have been classified using a new model-comparison-based algorithm that exploits the odds ratio principle to assign a probabilistic classification to each nebula in the sample. The resulting catalogue is the largest catalogue containing complete spectral and spatial information for a variety of ionised nebulae available so far in the literature. We developed this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 152 publications
(238 reference statements)
0
6
1
Order By: Relevance
“…We find a negligible difference when using KCWI Hβ in place of the MUSE Hβ flux. We should add that a recent investigation has shown that correcting, or not correcting, the Balmer lines for DIG contamination can impact the measured E(B − V ) (Congiu et al 2023). For the range of E(B − V ) observed, a DIG-corrected E(B − V ) may return values of A V 0.05-0.1 mag lower than presented here.…”
Section: Dust Correctioncontrasting
confidence: 45%
See 4 more Smart Citations
“…We find a negligible difference when using KCWI Hβ in place of the MUSE Hβ flux. We should add that a recent investigation has shown that correcting, or not correcting, the Balmer lines for DIG contamination can impact the measured E(B − V ) (Congiu et al 2023). For the range of E(B − V ) observed, a DIG-corrected E(B − V ) may return values of A V 0.05-0.1 mag lower than presented here.…”
Section: Dust Correctioncontrasting
confidence: 45%
“…We require the strong lines used for temperature determinations, namely Hβ, Hα, The constraints together remove 267 out of the 688 detected H II regions, leaving 421 H II regions remaining for use in future analysis. For these 421 regions, comparisons of line ratios in Figure 7 to model classifications in Figure 3 of Congiu et al (2023) suggest that this sample is consistent with their H II region classification. In order to compare the electron temperatures derived from the lines, which are critical for T e -T e comparisons, we also exclude regions with less than two significant (i.e., S/N > 3; see Section 5) detections in any auroral line.…”
Section: Quality Assessment and Classification Of Regionsmentioning
confidence: 54%
See 3 more Smart Citations